2007
DOI: 10.1111/j.1471-0528.2007.01468.x
|View full text |Cite
|
Sign up to set email alerts
|

Is misoprostol a safe, effective and acceptable alternative to manual vacuum aspiration for postabortion care? Results from a randomised trial in Burkina Faso, West Africa

Abstract: Objectives Previous research has demonstrated the effectiveness of misoprostol for treatment of incomplete abortion; however, few studies have systematically compared misoprostol's effectiveness with that of standard surgical care. This study documents the effectiveness of a single 600 micrograms dose of oral misoprostol versus manual vacuum aspiration (MVA) for treatment of incomplete abortion in a developing country setting.Design Open-label randomised controlled trial.Setting Two university teaching hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
97
1
12

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(125 citation statements)
references
References 17 publications
15
97
1
12
Order By: Relevance
“…This dose has successfully evacuated the uterus in over 1000 women in over a half a dozen trials worldwide. 9,10,19,20,11 Recently completed trials testing 400 mcg sublingual misoprostol compared to 600 mcg oral misoprostol found that that the 400 micrograms sublingual dose is as effective as 600 micrograms oral misoprostol when used for treatment of incomplete abortion. 22 Although the data in support of the 400 microgram sublingual misoprostol dose are less extensive, it may be shown in the future to be the optimal dose and route of administration for this indication.…”
Section: Dosage Regimen 11 17 18mentioning
confidence: 99%
See 4 more Smart Citations
“…This dose has successfully evacuated the uterus in over 1000 women in over a half a dozen trials worldwide. 9,10,19,20,11 Recently completed trials testing 400 mcg sublingual misoprostol compared to 600 mcg oral misoprostol found that that the 400 micrograms sublingual dose is as effective as 600 micrograms oral misoprostol when used for treatment of incomplete abortion. 22 Although the data in support of the 400 microgram sublingual misoprostol dose are less extensive, it may be shown in the future to be the optimal dose and route of administration for this indication.…”
Section: Dosage Regimen 11 17 18mentioning
confidence: 99%
“…5,9,10,12,14,19,20,[25][26][27][28][29][30][31][32][33][34][35][36][37][38]41 (Table 1) The success rate reported in trials is closely related to the length of time after treatment at which the uterus is reassessed by ultrasound exam. 16 Early studies on the use misoprostol for incomplete abortion tested a range of doses (400 mcg to 1200 mcg) and routes (oral, vaginal, intrauterine, etc.…”
Section: 2b Reports Of Efficacy From Studies Comparing Misoprostolmentioning
confidence: 99%
See 3 more Smart Citations